Sumak Kawsay, Feminisms and Post-Growth: Linkages to Imagine New Utopias (Alternautas, 2022)
This article explores the different understandings of gender that correspond to different concepts of sumak kawsay, tackling both ‘gender’ and ‘sumak kawsay’ as polysemous concepts. The article focuses specifically on the degrowth perspective, which is part of the ecological post-developmental understanding of sumak kawsay. It explores the implications that follow from these perspectives when questioning androcentric gender relationships. Additionally, the article exposes the meanings which the feminist economics of rupture attributes to the conceptual category of ‘the sustainability of life’, highlighting the overlaps and divergences with the post-growth understanding of that same category. The article defends the importance of resituating political and feminist debates under utopic horizons, such as those of sumak kawsay and post-growth.